2020
DOI: 10.3390/ph13100318
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Spatial Memory in 5xFAD Mice by Halting Cholinesterases, Oxidative Stress and Neuroinflammation Using a Cyclopentanone Derivative

Abstract: Alzheimer’s disease (AD) is an irreversible and chronic neurological disorder that gradually destroys memory and thinking skills. The research study was designed to investigate the underlying molecular signaling involved in the neuroprotective effects of cyclopentanone derivative i.e., 2-(hydroxyl-(3-nitrophenyl)methyl)cyclopentanone (3NCP) as a therapeutic agent for AD. In this study, In vivo studies were carried out on a well-known 5xFAD mice model using different behavioural test models such as open field, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…The effect of the Bergenin on the spatial learning and memory of 5xFAD Tg mice was evaluated through the Morris water maze apparatus (MWM, diameter: 110 cm, height: 40 cm) containing opaque water (depth: 20 cm) maintained at 22–23 °C, following previously reported method [ 61 ]. The maze consisted of four quadrants with a hidden platform (diameter: 7 cm, 1 cm below the water surface) in one of the four quadrants.…”
Section: Methodsmentioning
confidence: 99%
“…The effect of the Bergenin on the spatial learning and memory of 5xFAD Tg mice was evaluated through the Morris water maze apparatus (MWM, diameter: 110 cm, height: 40 cm) containing opaque water (depth: 20 cm) maintained at 22–23 °C, following previously reported method [ 61 ]. The maze consisted of four quadrants with a hidden platform (diameter: 7 cm, 1 cm below the water surface) in one of the four quadrants.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, the real promise of metabolic/ketogenic approaches is that by altering cellular energetics, oxidative stress, and inflammation, ketogenic (and possible 3NCP) have the potential to do more than provide symptomatic relief but also have the potential to alter disease trajectory. The cyclopentanone derivatives including 3NCP that were tested in our lab exhibited anti-cholinesterase, anti-oxidant, and anti-neuroinflammatory potential [23,24]. The 3NCP has a nitrophenyl group, and the literature studies revealed that compounds containing nitrophenyl group have the potential to inhibit AChE, BChE, MAO-B, and relieve oxidative stress [25].…”
Section: Introductionmentioning
confidence: 94%
“…Methodology of genotyping as specified by Jackson Lab U.S. for strain transgenic mice was followed with slight modifications [23]. DNA extraction was carried out by using a DNA extraction kit following the manufacturer's protocol.…”
Section: Genotyping Of 5xfad Micementioning
confidence: 99%
See 1 more Smart Citation
“…Agarose gel (1.5%) was used for amplified product separation. The mRNA expression was calculated in the arbitrary unit using ImageJ software (Ullah et al, 2020).…”
Section: Reverse Transcriptase Polymerase Chain Reactionmentioning
confidence: 99%